RENEWABLE GREEN RESOURCES - Axmedov Sultan Mukaramovich; Abdunazarov Shahzodbek O’tkirjon o’g’li; To’xtayev Samandar Alibek o’g’li (Journals Park Publishing, 2024)
This review will discuss the widespread use and economic attractiveness of chitin and chitosan. They can be extracted from crustacean waste, which is a stable source, and can be modified for specific applications. Valorization of crustacean waste has promising capabilities, chitin and chitosan have the potential to achieve the United Nations Sustainable Development Goals.
Keywords: Log in, Production, The path to UN sustainable development goals, Summary,Available literature